2020
DOI: 10.1126/scitranslmed.aat6263
|View full text |Cite
|
Sign up to set email alerts
|

Platelets from HIV-infected individuals on antiretroviral drug therapy with poor CD4 + T cell recovery can harbor replication-competent HIV despite viral suppression

Abstract: In addition to hemostasis, human platelets have several immune functions and interact with infectious pathogens including HIV in vitro. Here, we report that platelets from HIV-infected individuals on combined antiretroviral drug therapy (ART) with low blood CD4+ T cell counts (<350 cells/μl) contained replication-competent HIV despite viral suppression. In vitro, human platelets harboring HIV propagated the virus to macrophages, a process that could be prevented with the biologic abciximab, an anti–integrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
80
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(91 citation statements)
references
References 69 publications
8
80
1
2
Order By: Relevance
“…Although both DNA- and RNA-containing viruses associate with platelets, only RNA viruses are able to replicate, as platelets are incapable of DNA transcription due to their anucleate nature. A study on platelets isolated from human immunodeficiency virus (HIV)-infected patients on antiretroviral drug therapy (ART) revealed the occurrence of cytosolic HIV RNA and intact viral particles [ 105 ]. Noteworthy, replication competent viruses were only observed within closed vacuoles and not on the platelet surface.…”
Section: Composition and Sources Of Rna Species In Plateletsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although both DNA- and RNA-containing viruses associate with platelets, only RNA viruses are able to replicate, as platelets are incapable of DNA transcription due to their anucleate nature. A study on platelets isolated from human immunodeficiency virus (HIV)-infected patients on antiretroviral drug therapy (ART) revealed the occurrence of cytosolic HIV RNA and intact viral particles [ 105 ]. Noteworthy, replication competent viruses were only observed within closed vacuoles and not on the platelet surface.…”
Section: Composition and Sources Of Rna Species In Plateletsmentioning
confidence: 99%
“…This process was prohibited by blocking platelet–macrophage interactions with the platelet-specific anti-integrin α IIb /β3 antibody abciximab, underpinning the fact that viral spread is supported by intercellular interactions. Most interestingly, a low CD4 + T cell count was predictive for the presence of HIV-containing platelets in patients receiving ART, which correlated with immunological failure in these individuals [ 105 ]. In contrast, a recent study found no correlation of HIV + platelets with CD4 + T-cell count but with viral load and number of HIV + platelets were significantly reduced after ART.…”
Section: Composition and Sources Of Rna Species In Plateletsmentioning
confidence: 99%
“…Platelets are known to interact with viruses and have recently been shown to be transient carriers of HIV, thus contributing to HIV dissemination by propagating the virus to macrophages. This process could be prevented by the anti-integrin alphaIIb/beta3 antibody [ 56 ]. Coronaviruses may also infect bone marrow cells [ 55 ].…”
Section: Covid-19 Viral Sepsis and Phagesmentioning
confidence: 99%
“…In this context it is noteworthy, however, that human immunodeficiency virus 1 (HIV-1), which is also a single-stranded RNA virus, is not only internalised by platelets, but can also replicate in these cells. [49] This mechanism is operative in virally-suppressed, HIV-1-infected subjects and may represent a means of viral persistence and transmission. [49]…”
Section: Cytocidal Effects Of Sars-cov-2 On Plateletsmentioning
confidence: 99%
“…[49] This mechanism is operative in virally-suppressed, HIV-1-infected subjects and may represent a means of viral persistence and transmission. [49]…”
Section: Cytocidal Effects Of Sars-cov-2 On Plateletsmentioning
confidence: 99%